Generation of thiyl radicals in a spatiotemporal controlled manner by light: Applied for the cis to trans isomerization of unsaturated fatty acids/phospholipids - Biswajit Roy; Ryota Kojima; Obaed Shah; Meg Shieh; Eshani Das; Shahrzad Ezzatpour; Emiko Sato; Yusuke Hirata; Stephen Lindahl; Atsushi Matsuzawa; Hector C. Aguilar; Ming Xian (Redox Biology)
Thiyl radicals are important reactive sulfur species and can cause cis to trans isomerization on unsaturated fatty acids. However, biocompatible strategies for the controlled generation of thiyl radicals are still lacking. In this work, we report the study of a series of naphthacyl-derived thioethers as photo-triggered thiyl radical precursors. Tertiary naphthacyl thioether was identified to be a suitable template that could be used to produce both aryl and alkyl thiyl radicals under ultraviolet (UV) light or sunlight. The effective cis-to trans-isomerization of unsaturated fatty acid models (methyl oleate, methyl linoleate) and a natural phospholipid (cardiolipin) using these photo-triggered substrates was demonstrated. This reaction was also proved to proceed effectively in cells to produce thiyl radicals and subsequent fatty acid isomerization. Additionally, the most promising thiyl radical precursor showed antiviral activity in a pseudotyped virus model, likely due to disrupting viral lipid membranes upon UV activation. These findings highlight the potential of thiyl radicals for both biochemical and antiviral applications.